HEALTH LOCUS OF CONTROL, MEDICATION ADHERENCE AND QUALITY OF LIFE AS PREDICTORS OF DEATH ANXIETY AMONG PEOPLE LIVING WITH HIV/AIDS - Ojie Owen Isa; Joshua Edet Ifere; Peter Odey; Regina Onung Odey (GSC Advanced Research and Reviews, 2026)
Introduction: The diagnosis of an incurable disease can trigger a profound existential crisis as everyday life and the future are threatened for both patients and their families. As an existential issue, death anxiety stems from the conscious awareness of our own mortality. Aim: The study therefore attempts to examine the potential influence that health locus of control, medication adherence, and quality of life could have on death anxiety among HIV/AIDS patients. Methodology: The study utilized a cross sectional study design to recruit 120 people living with HIV/AIDs and receiving antiretroviral therapy in the ART unit of the General Hospital Ugep. The collected data was entered into a Microsoft Excel for initial processing. Subsequent analysis was conducted using the Statistical Package for the Social Sciences (SPSS) version 21.0. Quantitative variables were summarized and presented using means and standard deviations, while Hierarchical multiple regression was used to analyse the data for correlations. Results: There was a significant and positive correlation between medication adherence and death anxiety (r = -.20, p = .028). However, there was no significant correlation between quality of life and death anxiety. Also, medication adherence was a significant negative predictor of death anxiety (β = -.25, p< .015). quality of life did not account for any significant additional variance in death anxiety and did not also significantly predict death anxiety. Conclusion: Results showed that only medication adherence had a predictive negative relationship with death anxiety whereas health locus of control and quality of life did not have significant predictive relationships with death anxiety.